Normative performance data on visual attention in neurotypical children: virtual reality assessment of cognitive and psychomotor development - Goh, Crystal; Ma, Yu; Rizzo, Albert (Frontiers in Virtual Reality, 2024)
Virtual Reality (VR) is revolutionizing healthcare research and practice by offering innovative methodologies across various clinical conditions. Advances in VR technology enable the creation of controllable, multisensory 3D environments, making it an appealing tool for capturing and quantifying behavior in realistic scenarios. This paper details the application of VR as a tool for neurocognitive evaluation, specifically in attention process assessment, an area of relevance for informing the diagnosis of childhood health conditions such as Attention Deficit Hyperactivity Disorder (ADHD). The data presented focuses on attention performance results from a large sample (n=837) of neurotypical male and female children (ages 6-13) tested on a visual continuous performance task, administered within an immersive VR classroom environment. The results indicate systematic improvements on most metrics across the age span and sex differences are noted on key variables thought to reflect differential measures of hyperactivity and inattention in children with ADHD. This data was collected to create a normative baseline database for use to inform comparisons with the performances of children with ADHD to support diagnostic decision-making in this area. The results indicate that VR technology can provide a safe and viable option for testing attention processes in children under stimulus conditions that closely mimic ecologically relevant challenges found in everyday life. In response to these stimulus conditions, VR can support advanced methods for capturing and quantifying users' behavioral responses. VR offers a more systematic and objective approach for clinical assessment and intervention, and provides conceptual support for its use in a wide variety of healthcare contexts.